Survey Paper on Various Security Attacks In Mobile Ad Hoc Network - Selladevi, M; Duraisamy, S (International Journal of Computer Sciences and Engineering, 2025)
Mobile Ad-Hoc Network is a self-configured collection of cellular nodes in which there is no need of predefined infrastructure. In this network nodes can arbitrarily alternate their geographic places. MANET is more vulnerable to cyber-attacks than wired networks because of no any central coordination mechanism. Because of their dynamic topology, no infrastructure and no central management system MANETs are liable to various security attacks. In this paper we have proposed a solution to detect and prevent multiple attacks in a network and find a secure way to transfer data from source to destination node. This article briefly discusses about the concept of Mobile Ad Hoc Network (MANET) and its various types of attack and methods to solve the MANET attacks.